KAJIAN HUKUM ISLAM TENTANG KAMPANYE POLITIK SEBAGAI PEMBELAJARAN AKHLAK - Syafi'i, Ahmad; Mukarrom, Azmil (Jurnal Kajian Hukum Islam, 2019)
This research is literacy based on moral teachings and democrative values of Indonesian national leaders and expert opinion is further combined with the history of Islamic politics in the days of friends whose teachings in Islam as a reference for adherents to faith and the applicable provisions in the al-The qur’an and the Hadith of the Prophet and the ijma’ the ulamas’ and Qiyas in the future which are the ideal foundation as human beings who obey and obey the rules of the Islamic religion along with the teachings of their humanity values, thus each person can play a good personal and balance of course is closely related to ethics in politics, campaigning to demonstrate Islamic law in the real form is not just camouflage because besides personal relationships to the community but also to the Divine who is certainly every prospective candidate pays attention to the norms and values in Islam when agreeing with him n displaying the best without elemens of disdain, verbal abuse and mutual defamation, the information conveyed to the community remains in terms of the program and planning that is well adhered to morally and morals virtue in Islam.